2022
DOI: 10.30541/v54i2pp.79-96
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Management And Privatisations: Evidence From Pakistan Evidence From Pakistan

Abstract: This study examines the incidence of earnings management around the time of the privatisation of State Owned Enterprises in Pakistan during 1991-2005. Using the modified Jones model and a sample of large privatisations (minimum US$1 million), it shows that the sampled firms experienced increase in earnings, decrease in cash flows, and increase in current discretionary accruals in the year prior to and/or in the year of privatisation. The SOEs used both short term and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Likewise, prior studies document that firms whose CEO acts as the chairman of the board are likely to be a subject to enforcement actions by influential stakeholders for allegedly engaging in earnings manipulations (El Diri et al, 2020). For example, Klein (2002), Sarkar, Sarkar, and Sen (2008), Gulzar (2011), Roodposhti and Chashmi (2011), Soliman and Ragab (2014), Uwuigbe, Peter, and Oyeniyi (2014), Latif and Abdullah (2015); Iqbal, Khan, and Ahmed (2015); Al‐Haddad and Whittington (2019) suggest that CEO‐duality appeared to be positively associated with discretionary accruals manipulations. This implies that CEO‐duality improves the CEO's power and increases managerial discretion opportunities (Fama & Jensen's, 1983; Jensen's, 1993).…”
Section: Background Theory Empirical Literature Review and Hypothesis...mentioning
confidence: 99%
“…Likewise, prior studies document that firms whose CEO acts as the chairman of the board are likely to be a subject to enforcement actions by influential stakeholders for allegedly engaging in earnings manipulations (El Diri et al, 2020). For example, Klein (2002), Sarkar, Sarkar, and Sen (2008), Gulzar (2011), Roodposhti and Chashmi (2011), Soliman and Ragab (2014), Uwuigbe, Peter, and Oyeniyi (2014), Latif and Abdullah (2015); Iqbal, Khan, and Ahmed (2015); Al‐Haddad and Whittington (2019) suggest that CEO‐duality appeared to be positively associated with discretionary accruals manipulations. This implies that CEO‐duality improves the CEO's power and increases managerial discretion opportunities (Fama & Jensen's, 1983; Jensen's, 1993).…”
Section: Background Theory Empirical Literature Review and Hypothesis...mentioning
confidence: 99%
“…It is because, the initial shock of privatisation is over, and they can benefit in terms of better wages or of the increase employment opportunities. Iqbal, Khan, and Ahmed (2015) found that managers of the firms slated for privatisation were engaged in earnings management to inflate the financial worth of the firms to maximise the privatisation proceeds.…”
Section: Effect Of Privatizationmentioning
confidence: 99%